Late presentation of advanced abdominalpregnancy with live baby: A case reportand literature review - Abdullahi, Hauwa; Yakasai, Ibrahim; Zakari, Muhammed; Shuaibu, Samaila (Nigerian Journal of Basic and Clinical Sciences, 2026)
Abdominal pregnancy is a rare form of ectopic pregnancy. It is associated with an increase in maternal morbidity and mortality, as well as perinatal mortality rate of up to 85%-95%. A case of abdominal pregnancy in an unbooked primigravida who presented in the third trimester and was successfully managed is hereby described. She came with weight loss and jaundice. The fetus was alive and she was managed conservatively till a laparotomy was eventually performed. The outcome was good for mother and baby.